(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This experimental study examines the effectiveness of interactive teaching methods in developing students’ rational thinking. The paper presents the results of a pedagogical experiment conducted with 120 students during the 2023-2024 academic year. Modern interactive methods were used: case studies, business games, project work, discussions, and digital educational technologies. The results showed a significant improvement in rational thinking in the experimental group: critical thinking improved by 42%, analytical skills by 38%, and logical thinking by 45%. The study confirmed the hypothesis that the systematic use of interactive methods contributes to the development of sustainable rational thinking skills.